Cognitive intervention and its cultural components for people with dementia in Asia : a systematic review - Wani Amira Mustafa,; Ponnusamy Subramaniam,; Shazli Ezzat Ghazali,; Nor Afifah Aziz, (Penerbit Universiti Kebangsaan Malaysia, 2021)
People with dementia in the world is expected to increase to 139 million by the year 2050. Psychosocial approach has become a powerful tool to prevent cognitive decline due to aging effect in older adults. However, there is still lack of evidence on the psychosocial benefits of cognitive intervention on older adults with dementia in Asian countries. Therefore, the aim of this review is to synthesize latest evidence on the psychosocial benefit of cognitive intervention on Asian older adults with dementia. PubMed, Web of Science, and Scopus database have been used to aid the research. This review is limited to studies with randomized controlled trial (RCT) and controlled trial design. Nine randomized controlled trials out of 3897 studies have met the criteria for this review. Result revealed that cognitive intervention program is useful in improving global cognitive functioning of Asian older adults with dementia. Besides, cognitive interventions also significantly improve quality of life, depressive symptoms, and behavioural and psychological symptoms. Cognitive intervention as an alternate to pharmacological approach, can potentially benefit older adults with dementia. Future research should look further on the effects of cognitive intervention to specific cognitive domains such as attention, memory, executive function, and language as well as its usefulness in improving other areas of individuals’ functioning.